Newly isolated animal pathogen corynebacterium silvaticum is cytotoxic to human epithelial cells - Möller, Jens; Busch, Anne; Berens, Christian; Hotzel, Helmut; Burkovski, Andreas (International Journal of Molecular Sciences, 2021)
Corynebacterium silvaticum is a newly identified animal pathogen of forest animals such as roe deer and wild boars. The species is closely related to the emerging human pathogen Corynebac-terium ulcerans and the widely distributed animal pathogen Corynebacterium pseudotuberculosis. In this study, Corynebacterium silvaticum strain W25 was characterized with respect to its interaction with human cell lines. Microscopy, measurement of transepithelial electric resistance and cytotoxicity assays revealed detrimental effects of C. silvaticum to different human epithelial cell lines and to an invertebrate animal model, Galleria mellonella larvae, comparable to diphtheria toxin-secreting C. ulcerans. Furthermore, the results obtained may indicate a considerable zoonotic potential of this newly identified species.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Caseous lymphadenitis; Diphtheria; Diphtheria toxin; Host-pathogen interaction; Macrophage; Vero cells; Zoonosis